Adverse drug reactions in older patients: an Italian observational prospective hospital study - Conforti A; Costantini D; Zanetti F; Moretti U; Grezzana M; Leone R (Drug, Healthcare and Patient Safety, 2012)
Anita Conforti,1 Davide Costantini,1 Francesca Zanetti,2 Ugo Moretti,1 Matteo Grezzana,2 Roberto Leone11Department of Public Health and Community Medicine, Section of Pharmacology, University of Verona, Verona, Italy; 2Third Division of Geriatrics, Verona University Hospital, Verona, ItalyBackground: In adults over 65 years of age, the frequency of adverse drug reaction (ADRs) related hospital admissions is higher than in younger adults, and the frequency of ADRs occurring during hospital stay highly ranges. The review was designed to evaluate the frequency of ADRs, both resulting in hospital admission and occurring during the hospital stay of older patients, while identifying the types of reactions and the associated drugs.Methods: Age, sex, date, and diagnosis of admission of all patients aged 65 and over admitted in three geriatric wards of University Hospital of Verona, Italy, from February to July 2009 were registered by nurses on a special form. In the specific cases of admissions caused by an ADR as well as in the cases of an ADR occurring during the hospital stay, the type of reactions and the suspected drugs were also registered by nurses and physicians involved in the study.Results: During the six months of the study, 1023 patients matched the inclusion criteria and were included in the study. One hundred fourteen hospital admissions (11.1%) were caused by ADRs, while 256 patients (25.0%) had an ADR during their hospital stay. The duration of hospital stay was significantly longer in patients who developed an ADR during their time in hospital, 18.7 (95% CI: 17.2–20.1) days versus 12.6 (95% CI: 11.9–13.3) days. Electrolyte disorders, gastrointestinal disorders, anemia, and International Normalized Ratio increase were the more frequent observed ADRs, with diuretics, antithrombotic agents, and antibacterials as the main involved drugs. Our study confirms that ADRs are an important cause of hospitalization in older patients. In addition, the frequency of ADRs occurring during hospital stay is high and causes prolonged hospitalization.Keywords: adverse drug reaction, anemia, electrolyte disorders, hospital admission, hospital stay, older patients, gastrointestinal disorders